Quality of artificial rain to overcome clean water crisis: A review on several parameters - Agustin, Dhini; Santoso, Fadhila Zahra; Sajidah, Salmaa Nabiilah; Priyandoko, Didik; Surtikanti, Hertien Koosbandiah (Institute for Advanced Science, Social, and Sustainable Future, 2024)
Water is the most important substance needed by living things apart from air. Long droughts have serious impacts on society and the environment resulting in a lack of clean water supply, both in terms of quality and quantity. The purpose of the article is to contribute to a better understanding of overcoming the clean water crisis by utilizing artificial rain. The method of writing this article is a literature study on several journals and previous articles to obtain data and information to review experiences that have been successfully carried out in previous studies. The parameters used are pH, DHL, Sulfate, and Ca. Based on the study data, the pH is 6-8 which is still safe for drinking water consumption and fisheries, the DHL parameter is not recommended for drinking water consumption because it contains electric charge and is not recommended for agriculture and fisheries because it has high DHL levels. Sulfate is considered safe because it has low levels. In general, the presence of sulfate does not have a significant impact on health because the nature of sulfate ions is quite stable and does not react easily. Both high and low Ca levels are still considered unsafe. Only pH and Sulfate levels are classified as safe for agriculture, fisheries, and as drinking water.